Exploring changes in mobility experiences and perceptions after implementation of the bus rapid transit system in Dar es Salaam. Issue 2 (June 2021) - Joseph, Lucy; Neven, An; Martens, Karel; Kweka, Opportuna; Wets, Geert; Janssens, Davy
Highlights: The study provides insights about changes in mobility experiences/perceptions before and after BRT implementation in Dar es Salaam (DES). The study employed FGDs to understand the mobility benefits of IPT and BRT use from local people's perspectives. Meeting the mobility demands of diverse users is unrealistic by the BRT system alone in areas with a high level of informality. BRT seems to overlook the complex trip-making of the urban poor and the implications of the system. Abstract: The use of Informal Public Transport (IPT) in Dar es Salaam, Tanzania, has been associated with mobility difficulties, i.e. traffic congestion, unscheduled service and lack of safety and security. The introduction of the Bus Rapid Transit (BRT) system was therefore considered as a powerful intervention for these mobility difficulties. In May 2016, the BRT started operating with exclusive bus lanes and a clear schedule to offer a qualitative, accessible and affordable system. This paper explores changes in travel experiences and perceptions of individuals (local inhabitants) regarding IPT and BRT use in meeting mobility demands before and after implementation of the BRT. Focus group discussions and short questionnaires were conducted before and after BRT to explore changes in mobility experiences among different individuals. Results show that in both periods, the demand for IPT use remained dominant, driven by a low fare, connectivity within a neighbourhood and outside the major road, flexibility and the possibility to commute with goods. The use of BRT was mainly attributed by relief in traffic congestion (when only considering in-bus time) and a lack of options along the corridor. Surprisingly, BRT users also experienced several mobility difficulties after implementation: long waiting time, overcrowding (in-bus and stations), and difficulties to commute with goods, and a lack of safety and security. Peri-urban individuals continued to experience more travel difficulties with both transport systems than individuals in areas adjacent to the BRT because of limited connectivity, congestion and unpaved local roads. For low-income individuals, the BRT was considered as another burden for their livelihoods (higher financial cost) rather than it was expected as a solution towards a high quality, accessible and affordable system. There is a need to integrate public transport with supportive improved local roads to serve multiple destinations.